A novel reference chart and growth standard of fetal biometry in the Taiwanese population - Tsai-Ming Huang; Chin-Han Tsai; Fang-Yu Hung; Ming-Chao Huang (Elsevier, 2022)
Objective: The purpose of this study was to establish a new reference chart and growth standards for fetal biometry in Taiwan. Materials and methods: 2047 singleton pregnancies were enrolled in this study with 15,813 fetal scans between 18 and 40 gestational weeks. A reference chart and normal range for fetal biparietal diameter (BPD), abdominal circumference (AC) and femur length (FL) was established by longitudinal quantile regression model. 330 women with comorbidities including gestational hypertension, preeclampsia and gestational diabetes were excluded and 1717 pregnant women were enrolled for the growth standard. Results: The new reference values were significantly larger across all gestational ages compared with the prior National Taiwan University reference chart in 1983. Compared with Intergrowth-21st, the BPD was larger at 18-23 weeks, the AC was larger at 18-24 weeks and the FL was larger at 18-36 weeks whereas they were all smaller at 29-40 weeks for the BPD, at 32-40 weeks for the AC and at 38-40 weeks for the FL. A quantile regression equation of biometry was established. BPD, AC, and FL had weekly growth of 2.5, 9.87 and 2.15 mm. Prepregnancy body weight, height, age, and gestational diabetes increased fetal size. Both gestational and chronic hypertension decreased fetal size. Conclusion: To promote maternal-fetal safety, a new reference chart and growth standard for fetal biometry is necessary to measure fetal growth.